2013
DOI: 10.1111/luts.12043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Male Urinary Incontinence on Health‐Related Quality of Life: A Population Based Study

Abstract: Urinary incontinence affects men's QoL negatively. In particular, mixed urinary incontinence has the greatest impact on QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Published UI prevalence estimates vary widely, due at least in part to differences in UI definition and sampling strategies (for example face-to-face, phone or internet surveys). 28 In Asia (China, Taiwan and Korea), UI prevalence has been studied predominantly in populations that include young adults at a lower risk of UI than older individuals [9][10][11][29][30][31][32] and in women, 9,10,12,13,29,30 with few data available for men alone 11,33 or for both genders. 31,32 Not all studies report prevalence of UI subtypes, 9,13 Note: Numbers of individuals are weighted and rounded, and hence may not add up; percentages are based on the weighted "n" values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published UI prevalence estimates vary widely, due at least in part to differences in UI definition and sampling strategies (for example face-to-face, phone or internet surveys). 28 In Asia (China, Taiwan and Korea), UI prevalence has been studied predominantly in populations that include young adults at a lower risk of UI than older individuals [9][10][11][29][30][31][32] and in women, 9,10,12,13,29,30 with few data available for men alone 11,33 or for both genders. 31,32 Not all studies report prevalence of UI subtypes, 9,13 Note: Numbers of individuals are weighted and rounded, and hence may not add up; percentages are based on the weighted "n" values.…”
Section: Discussionmentioning
confidence: 99%
“…5 In an analysis of the National Social Life, Health and Aging Project undertaken in US adults from 2010 to 2011, UI was one of the most significant contributors to poor mental health for women. 8 A number of studies undertaken in Asia have also demonstrated the negative association of UI with health-related quality of life (HRQoL)/mental health, [9][10][11][12][13][14][15][16][17][18] reporting a substantial impact that can be similar to or greater than that caused by other chronic medical diseases, such as diabetes, hyperlipidemia, and chronic kidney disease. 13,19 Despite this, a large proportion of individuals with UI do not seek treatment for their symptoms 20,21 and of those who receive pharmacotherapy, many are dissatisfied and discontinue medication.…”
mentioning
confidence: 99%
“…It is defined as urinary urgency with or without urgency urinary incontinence and is usually associated with increased daytime frequency and nocturia (3). OAB has considerable impact on health-related quality of life (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that UI is common, and adversely affects QoL . UI has manifold implications for sufferers, including increased risk of depression and anxiety and poorer life satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that UI is common, and adversely affects QoL. [1][2][3] UI has manifold implications for sufferers, including increased risk of depression and anxiety and poorer life satisfaction. 2 Although UI can often be improved, a substantial number of people who seek help for their UI will continue to experience episodes of urine leakage following treatment.…”
mentioning
confidence: 99%